2015
DOI: 10.3748/wjg.v21.i42.12150
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic role of p21 in hepatocarcinogenesis suggests a new treatment strategy

Abstract: A well-known tumor suppressor, p21, acts paradoxically by promoting tumor growth in some cellular conditions. These conflicting functions have been demonstrated in association with the HBx gene and in hepatocarcinogenesis. The molecular behavior of p21 depends on its subcellular localization. Nuclear p21 may inhibit cell proliferation and be proapoptotic, while cytoplasmic p21 may have oncogenic and anti-apoptotic functions. Because most typical tumor suppressive proteins also have different effects according … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 77 publications
1
21
1
Order By: Relevance
“…In the present study, no effect on cell cycle was observed following c-Myc inhibition, which suggests that synergistic action with another signaling pathway may be required for its role on cell proliferation. c-Myc is an oncogene and p21 is a tumor suppressor gene (28). In the present study, c-Myc was demonstrated to promote RMS development by repressing p21 transcription.…”
Section: Discussionsupporting
confidence: 54%
“…In the present study, no effect on cell cycle was observed following c-Myc inhibition, which suggests that synergistic action with another signaling pathway may be required for its role on cell proliferation. c-Myc is an oncogene and p21 is a tumor suppressor gene (28). In the present study, c-Myc was demonstrated to promote RMS development by repressing p21 transcription.…”
Section: Discussionsupporting
confidence: 54%
“…As miRNAs mainly function through directly suppressing the translation of their target genes (27), the potential target genes of miR-93 in osteosarcoma were then examined. Among the putative target genes of miR-93, P21 is a key regulator of cell cycle progression at the G1 checkpoint (28). In addition, P21 can also interact with proliferating cell nuclear antigen, a DNA polymerase accessory factor, and has a regulatory role in S phase DNA replication and DNA damage repair (29).…”
Section: Discussionmentioning
confidence: 99%
“…In this experiment, stress and drug treatment increased its expression (and despite it being an HSP90 client). The cell cycle inhibitors p21/CDNK1A/CIP1/WAF1 and p27/CDKN1B/KIP1 also have pro- and anti-apoptotic functions depending on subcellular localization and mutation status [62–64]; here, their expression increases with stress and drug applications.…”
Section: Resultsmentioning
confidence: 99%